Andra Soni and Airin's Speech Strategy in the 2024 Banten Provincial Election - Nabilia Jayabaya, Zamzarra; Fauzi, Aziz (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Campaign activities are a moment that is very much used by each candidate pair. Each pair of candidates will try to convince the public to vote for them. The process of conveying ideas will not be successful if you do not use interesting communication methods. The purpose of this study is to find out what types of speech acts are used by the pair of candidates for Governor of Banten while running the campaign. The method used is qualitative. Data was obtained using the note-and-listen technique. In addition, the data analysis technique in this study has many stages, such as data collection, presentation of raw data, data reduction, data categorization, and making conclusions from tested data. The findings in this study show that there are five speech acts used, such as assertive, declarative, commissive, directive, and expressive speech acts.